Discursos e representações sobre a cidade na década de 1930: as crônicas do Jornal Diário dos Campos e o álbum de Ponta Grossa - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
A research proposes an analysis of the journalistic and photographic production on the urban space in Ponta Grossa in the 1930s. As sources used are chronic kinetics of the newspaper Diário de Campos and the 1936 Ponta Grossa Álbum. As chronicles they discuss supposed problems affected by the tax cutting-edge period, at a time of reorganization of the urban space promoted in the city in those decades. The texts demonstrate the speeches issued by the newspaper about Ponta Grossa and examine how the chronicler positions himself after this process and, mainly, how they perceive those who do not fit the intended city model - modern and civilized, like the minors who lived on the streets, the residents who do not comply with the rules for new construction or the traders who were at fault with the hygiene rules applied by the Municipal Postures, among other variables. Starting from the themes discussed in the chronicles, a research seeks to define dialogue with a set of photos produced by Ewald Weiss to compose the Ponta Grossa Album of 1936, prioritizing as photographs on an urban theme. Therefore, analyze the different representations built by sources about space and Ponta-Grossense society, and how the ideals of modernity, order and civility were disseminated in an attempt to build an imaginary and memory of the modern city, or civilization. There is still a pedagogical didactic material contemplating the results of the research, with suggestions of activities and methods for the use of elementary and high school teachers, to address the theme of local history and the use of sources in the classroom.
Keywords: ensino de história; espaço urbano; jornal; fotografias; história local; history teaching; urban space; newspaper; photographs; local history; CNPQ::CIENCIAS HUMANAS::HISTORIA